Isolation, identification and characterization of Leuconostoc mesenteroides as a new probiotic from intestine of snakehead fish (Channa striatus) - Allameh, Sayyed Kamaleddin; Mohd Daud, Hassan; Md Yusoff, Fatimah; Saad, Che Roos; Ideris, Aini (Academic Journals, 2012)
The intestinal microflora of snakehead (Channa striatus) fish was studied to isolate and identify lactic acid bacteria as new probiotic. A total of five lactic acid bacteria were isolated from intestine to evaluate with probiotic properties. Leuconostoc mesenteroides sp. mesenteroides with more ability to inhibit growth of Aeromonas hydrophila was selected and identified by conventional and molecular techniques. This strain was able to survive and grow from pH 3 to 8 with the highest viability and growth rate at neutral conditions (pH 7). In addition, L. mesenteroides tolerated 0, 0.15 and 0.3% bile salt concentrations. This bacterium also, showed inhibitory activity against three tested fish pathogens which included; A. hydrophila, Pseudomonas aeruginosa and Shewanella putrefaciens. Antibiotic sensitivity test indicated that this strain was resistant to Streptomycin, intermediate to Amoxicillin and Kanamycin and sensitive to Gentamycin, Tetracycline, Chloramphenicol, and Ampicillin.